FUN AND EFFECTIVE INDONESIAN LANGUANGE LEARNING FOR STUDENTS IN ELEMENTARY SCHOOL - Nurfitria; Novi Ardilah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In the era of development and technological advances affecting the quality of student learning tends to decline. This can also affect classroom learning to be less effective and enjoyable. The learning objectives that have been made by the teacher will not be achieved. So the efforts made by the teacher to improve the quality of learning that is effective and enjoyable, the teacher chooses the right method in learning science for class IV SD. The method used is the demonstration method where the demonstration method is known as a method that can involve students directly in learning. The results of this research state that science subjects are one of the mandatory subjects implemented in elementary school education units. Where science subjects are subjects related to natural knowledge and must be studied by elementary school education units. To increase learning that is fun and not boring for students, teachers must use the right methods in learning, the right methods to apply to students.